Cultural & region-specific adaptation of KAP (Knowledge, attitude, and practice) tool to capture healthy lifestyle within primary care settings. - Ahmed Sameer Alnuaimi; Muslim Abbas Syed; Abduljaleel Abdullatif Zainel; Hafiz Ahmed Mohamed; Mohamed Iheb Bougmiza; Mohamed Ahmed Syed (PLoS ONE)
Background Non-communicable diseases contribute to a significant global burden of disease and are associated with modifiable risk factors such as physical inactivity, unhealthy diet, tobacco use and excessive alcohol consumption. These risk factors are closely related with lifestyles and eating patterns which are often culturally embedded and managed differently in various health care settings. Aim of the study To assesses the applicability and feasibility of the KAPS (Knowledge, attitude, and practice) survey in generating data about knowledge, attitudes, and practices about healthy lifestyles within eastern Mediterranean settings and providing foundations for testing other models or development of a newer model in this area which captures and influence behavior changes towards healthy lifestyles. Methods The KAP survey was tailored to capture the construct of healthy lifestyles (within the context of Qatar primary care settings) by reviewing existing surveys, adaptation to local context, expert consultation and feedback, pilot testing, feedback analysis, cognitive interviews and translation and validation. Results The study reports that most participants found the content comprehensive, relevant, easy to understand but considered it lengthy. Analysis of grading of the 73 questionnaire items (complete questionnaire included as supplementary document) included by the panel of experts (n = 13) demonstrated that more than half of questions (52.1%) have a CVR value of 1. Thematic analysis of overall perceptions of the service users (n = 11) pertaining to the feasibility of the KAP survey identified three important themes which included i) clarity & readability of the questions ii) relevance of the instrument and iii) factors influencing service users' participation in survey. Conclusion A culturally sensitive and region specific KAP tool specifically designed for healthy lifestyles can aid in health advocacy, monitoring modifiable risk factors, capturing rich epidemiological data to design preventive interventions, surveillance of high risks patients and strengthening the existing health information systems. Further research is needed to explore evidence-based methodologies to formulate an age-specific and shorter version of KAPs survey without compromising the validity of the tool within specific regional primary healthcare settings.